Method Development for Estimation of Azelnidipine and S (-) Metoprolol Succinate in Tablets by UV Spectrophotometry and HPLC Using Student’s T-Test - Ganorkar, Saylee; Bhavsar, Aditya; Khiste, Rahul (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: Azelnidipine a calcium channel blocker belongs to BCS class II and S (-) Metoprolol Succinate belongs to BCS class I. Rationale: Calcium is responsible for inducing smooth muscle contraction. Inhibiting calcium channel will inhibit the contraction of smooth muscles which results in reduction of blood pressure. Metoprolol selectively acts on β-1adrenergic receptor (specifically related to cardiac cells). Metoprolol shows negative ionotropic and chronotropic effect. Thus, it shows synergistic or complementary action azelnidipine. Objectives: To formulate and evaluate the new combination of antihypertensive drugs and UV and reverse phase chromatography method development for quantification of Azelnidipine and Metoprolol in its formulation. Materials and Methods: For the simultaneous estimation of Azelnidipine and S (-) Metoprolol Succinate by UV-spectrophotometry two UV-spectrophotometric methods were developed using Schimadzu-1800 UV spectrophotometer. RP-HPLC method was developed using Inertsil ODS C18 (150X4.6 mM; 5 μM) column by flowing solvent system sodium dihydrogen phosphate anhydrous Buffer: Acetonitrile (35:65) at the 1 mL/min. Detection of chromatographic peaks were carried out by employing a 235 nm UV detector. Results: According to ICH recommendations, the developed methods were validated. The suggested technique demonstrated appropriateness for concurrent determination of azelnidipine and metoprolol using a UV spectrophotometer and HPLC. Conclusion: The method established via UV-Spectrophotometry and HPLC was evaluated to be unique, easy, accurate and exact. The technique can be applied to routine quality control of bulk and combined dose forms of Azelnidipine and S (-) Metoprolol Succinate in pharmaceutical and drug research laboratories
Keywords: Azelnidipine; Metoprolol; RP-HPLC; UV-Spectrophotometry